SIGNIFICANCE OF ISLAMIC FINANCE IN FINANCIAL MARKET OF UZBEKISTAN (Innovative Technologica: Methodical Research Journal, 2023)
In this article, the following activities are listed as being against Islamic finance.Islamic finance is an increasingly popular alternative to conventional finance, rooted in principles of the Islamic faith. It prohibits interest-based transactions, speculative transactions, and investments in unethical industries. Instead, it emphasizes profit-and-loss sharing, ethical investing, and social responsibility. Islamic finance offers a range of products, including sukuk, murabaha, takaful, Islamic investment funds, and microfinance. These products promote ethical and socially responsible financial practices and provide access to financial services for those excluded from conventional finance. However, their complex Shariah-compliant structures and lack of a standardized regulatory framework in some jurisdictions pose limitations. Islamic finance has significant economic implications, including promoting financial inclusion and poverty reduction.